THe Innovative Reminder in Senior-Focused Technology (THIRST)—Evaluation of Serious Games and Gadgets for Alzheimer Patients - Eichhorn, Christian; Plecher, David A.; Lurz, Martin; Leipold, Nadja; Böhm, Markus; Krcmar, Helmut; Ott, Angela; Volkert, Dorothee; Hiyama, Atsushi; Klinker, Gudrun (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2019)
We investigate the combination of a drinking gadget with Serious Games, designed to entice elderly/dementia patients to drink more water - with potential benefit for both, the elderlies and their caregivers. We present several strategies that are essential towards developing a Combined Evaluation Process needed to determine user acceptance. We report on a pilot study conducted in a retirement home with dementia patients. The goal was to gain first insights regarding the acceptance of such a technology from the viewpoint of the elderly and their caregivers.
CRIS-Team Scopus Importer:2019-08-06
Keywords: Alzheimer patients; Caregivers; Dehydration; Dementia; Drinking detection; Gadgets for elderly; Retirement home; Serious Games